IN-VIVO ANTI-PLASMODIAL ACTIVITY AND IN-VITRO ANTIOXIDANT PROPERTIES OF METHANOLIC LEAF EXTRACT OF AZADIRACHTA INDICA AND ITS POSITIVE EFFECT ON HEMATOLOGICAL AND LIPID PARAMETERS IN SWISS ALBINO MICE INFECTED WITH PLASMODIUM BERGHEI NK 65. - Momoh. J.; Longe. A.O; Aina. O.O.; Ajibaye. O. (European Scientific Journal, ESJ, 2015)
The study was conducted to determine the effect of in vivo anti-plasmodial and in vitro antioxidant properties of methanolic leaf extract of Azadirachta indica and its positive effect on hematological and lipid parameters in Swiss albino mice infected with Plasmodium berghei NK65. Swiss albino mice were inoculated intraperitoneally with Plasmodium berghei NK65. The mice were grouped into six groups, five per group. Group I were not infected with P.berghei, Group II and III served as both the negative and positive control while Group IV, V, and VI were treated with 200, 400, and 800 mg/kg body weight of methanolic leaf extract of A. indica. The secondary metabolites in the extract include tannin, flavonoids, glycosides and saponin etc. The extract does not have any toxic effect that can lead to the death of the animals. The median lethal dose LD50 was estimated to be >5000mg/Kg body weight. The extract caused 47.80%, 50.96% and 52.30% suppression in parasitaemia at 200, 400 and 800mg/kg body weight respectively while Chloroquine exerted 100% suppression at 5mg/kg body weight. The curative test shows that the different concentration of the extract exert a growth inhibition of 50.1%, 74.57% and 73.68% at 200, 400, 800mg/kg body weight respectively while Chloroquine cleared the parasites by 94.07% at 5mg/kg body weight. The Hematological parameters showed that the extract is not hematotoxic since it significantly increase (P<0.05) RBC, HGB, and HCT values while their WBC count reduced significantly when compared to the infected untreated mice. There is a significant decrease (P<0.05) in plasma TC, TG and LDL-C in the treated groups and their HDL-C significantly increase when compared to infected untreated group. This study shows that A.indica extract has hypolipidemic effect. In the in-vitro antioxidant assay, the extract significantly increase (P<0.05) the level of SOD, CAT and GSH in the liver homogenate induced with oxidative stress using H2O2 while the MDA values reduced significantly with the administration of the extract of A.indica.